The Brazilian Ayahuasca Religions - Wright, Robin Michel (Fieldwork in religion, 2006)
This article reviews the forthcoming issue of FIR containing an important collection of articles on the origins and developments of religious movements and, later, research movements focused on a powerful psychoactive beverage consisting of the mixture of certain vines (ayahuasca) and leaves (chacrona) found mainly in Western Amazonia. The religious interpretations resulting from the ritual ingestion of the beverage have produced the most varied practices and beliefs, beginning with the indigenous peoples and mestizo herbalists, then migrant rubber-tappers from northeastern Brazil; in the 1960s, urbanites from major cities in Brazil and Europe seeking alternative forms of religious inspiration; and, in the 1990s, a group of Brazilian researchers who have combined anthropological and religious understanding of the phenomena along with legal expertise for the protection of the religious freedom necessary for the religions' developments. With the diversification and globalization of these new religious movements, the article points to new directions for field research in these religions.